A pilot evaluation of the Baby Social ABCs caregiver-mediated intervention for 6–15-month-olds with early signs of autism—feasibility, acceptability, and preliminary evidence - Dowds, E.; MacWilliam, S.; Solish, A.; Osten, S.; Zwaigenbaum, L.; Smith, I. M.; Brian, J. A. (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundAutism spectrum disorder (autism) is a neurodevelopmental condition with a high prevalence of approximately 1 in 50 children. Early intervention can support long-term outcomes. Caregiver-mediated interventions (CMIs) are evidence-based and appropriate for toddlers with autism or early social communication challenges. The Social ABCs, one such CMI, is supported by robust evidence. Originally developed for toddlers (12–42 months), it shows potential for supporting social communication development even earlier, i.e., for infants with early signs of autism. The current project adapted the toddler Social ABCs for use with infants (aged 6–15 months) showing early signs of autism or with a confirmed diagnosis. This paper describes the development, acceptability, feasibility, and preliminary outcomes for the Baby Social ABCs.MethodsNine infants (aged 6–14 months) participated. Families either self-referred or were referred by community clinicians and were eligible based on age and clinician and/or parent concerns about social communication and/or behavioral differences. Each infant and one of their primary caregivers participated in the 12-week Baby Social ABCs intervention online via Zoom for Healthcare.ResultsCaregiver implementation fidelity increased significantly, along with infant responsivity and social communication behaviors (social orienting, shared smiling, and gesturing). The caregivers reported high satisfaction with the coaching approach, session structure, and curriculum.DiscussionThis pilot study demonstrated the feasibility and acceptability of the Baby Social ABCs as a novel CMI for infants with signs of emerging autism and showed promising effects on the caregivers’ fidelity and the infants’ social communication and engagement. Future research should consider the optimal timing (or personalized “fit”) for families to access such support to better understand the type and intensity of pre-diagnostic care that best meets families’ diverse needs.